Invisible Seasons : Title IX and the Fight for Equity in College Sports - Belanger, Kelly (Book collections on Project MUSE., 2016)
In 1979, a group of women athletes at Michigan State University, their civil rights attorney, the institution?s Title IX coordinator, and a close circle of college students used the law to confront a powerful institution-- their own university. By the mid-1970s, opposition from the NCAA had made intercollegiate athletics the most controversial part of Title IX, the 1972 federal law prohibiting discrimination in all federally funded education programs and activities. At the same time, some of the most motivated, highly skilled women athletes in colleges and universities could no longer tolerate the long-standing differences between men's and women's separate but obviously unequal sports programs. In Invisible Seasons, Belanger recalls the remarkable story of how the MSU women athletes helped change the landscape of higher education athletics. They learned the hard way that even groundbreaking civil rights laws are not self-executing. This behind-the-scenes look at a university sports program challenges us all to think about what it really means to put equality into practice, especially in the money-driven world of college sports.